ENT300 Bubbles and Bleach Laundry / Diana Anak Manggie... [et al.] - Manggie, Diana; Pailin, Dir Hamdi; Abg Mat Ali, Dyg Siti Humaira; Ahmad Shamizan, Erra Fazzierah; Naing, Nur Farizah Filzah (2015)
Our company name is BUBBLES AND BLEACH COMPANY. The business is in the form of partnership which is consisting of five members. Each partner contributes amount of cash agree in our agreement. Our main business is providing coin operated self-service laundry. Although there are many bigger company outside there that also open a laundry as their business, but we confident that our business can be success in the future. Our business aimed to get the customer to be more familiar to the business and make sure our customer will be easy to get laundry services at any time.